Bluetooth Platform for Wireless Measurements Using Industrial Sensors. (29th January 2013) - Tašner, Tadej; Les, Kristian; Lovrec, Darko
The past decade has seen significant advancement in the field of mobile devices. Various smart devices such as cellular phones, tablets and PDAs have become universal tools in our everyday lives. Their versatility is based on their computing power, portability and their integration with other devices and services such as the World Wide Web. However, these smart devices have an even wider usability spectrum. They can also be used for wireless industrial measurements using existing sensors. The wireless connectivity of existing industrial sensors is achieved by equipping them with a Bluetooth module, which digitizes the data and passes it to any Bluetooth capable smart device for further processing, evaluation and logging. This paper describes the specially designed Bluetooth platform for wireless measurements all the way from the basic concept, through hardware, firmware and software implementation, to the sample tests and measurements.